Getting back on track: control of covid-19 outbreaks in the community. (25th June 2020) - Roderick, Peter; Macfarlane, Alison; Pollock, Allyson M
Abstract : Peter Roderick, Alison Macfarlane, and Allyson M Pollock argue there's still time to change tack on the UK's ad hoc system for covid-19 tracking, testing, and contact tracing